Relationships between Christian Schools and the State : A Comparative Analysis for Five sub-Saharan African Countries - Scheunpfluga, Annette; Wenz, Mark; Rubindamayugi, Mimii Brown; Lutswambac, Jean Kasereka; Njobatid, Frederick; Nyiramanae, Christine; Mutabazi, Samuel; Njoyaf, Claude Ernest; Raharijaonag, Onja; Wodonh, Quentin (Taylor and Francis, 2022)
This article provides a comparative analysis of Christian faith-based schooling in five African countries, including data on the proportions of faith-based schools, financing models, and forms of organization vis-à-vis the state. The case studies represent different forms and models. In all of the countries, at least one in six schools is run by a church. Christian churches do not see themselves as ‘private schools’ but as public providers working for the public common good. Faith-based schools contribute not only to making sure that children go to school and learn while in school, but also to sharing ideals ranging from social justice and equity, to peace and democracy, and social participation and inclusion. The article concludes with some reflections on future challenges for faith-based schools, mainly related to their funding and the lack of data to assess challenges and opportunities.